Reka Bentuk Rumah Teres Dua Tingkat yang Berasaskan Elemen Hijau bagi Kos Sederhana - Mohamad, Aini Nadirah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2022)
A greenhouse building is a house that is environmental friendly, healthy, and comfortable. However, the construction capital of terrace houses, especially the medium-cost type of two-storey based on green element design, is too high due to complex design, and as a result, developers have to offer expensive prices, causing buyers to not be able to own a house. Therefore, the objective of this study is to examine the design criteria often taken into account by developers when building green element-based medium-cost two-storey terrace houses, to study the main tastes of buyers of green element-based medium-cost terrace houses. The scope of the study involved developers and buyers of two-storey terrace houses based on medium-cost green elements in Johor, a total of 18 respondents, consisting of 5 developers and 13 buyers. A qualitative approach was used by interviewing developers and buyers through the Google Meet app. The results of the study found that the design criteria most often taken into account by developers are environmentally resource efficient processes and for innovation design is Integrated Photovoltaic Technology (BIPV), while the criteria of buyer taste are centred on a healthy home. In conclusion, this study can help developers get a realistic idea of how to design a house based on green elements at a moderate cost and can meet the tastes of affordable buyers.